Human Capital Planning in the Business of X-ray Screening Detection System: Human Resource Competency and Efficiency Development Strategy - Gunawan, Wawan Iwan; Indradewa, Rhian; Nugroho, Sukmo Hadi; Kustiawan, Unggul (Universitas Pahlawan Tuanku Tambusai, 2025)
The role of human capital in the healthcare industry is crucial, especially in high-tech based services such as the Clinic X-ray Screening System. This research aims to design human resource (HR) planning in accordance with operational needs, safety standards, and customer satisfaction in the radiology clinic business. This study uses descriptive-qualitative methods and Human Resource Planning (HRP), Job Analysis, and Human Capital Readiness Index (HCRI) analysis approaches. The results of the study show that the technical competence of radiology operators, the soft skills capabilities of service personnel, and clinical leadership are the three main pillars in supporting the efficiency and quality of services. The study suggests competency-based recruitment strategies, ongoing training, as well as productivity measurement based on key performance indicators (KPIs)